Review of the Relationship between Anti-Hypertensive and Anti-Diabetes Drugs with Psychiatric Disorders - Farzaneh Hasani Sadi; Farnaz Saberian; Mahdieh Tajik; Bita Fallahpour (Novelty in Biomedicine, 2025)
Background: Diabetes and hypertension are two common diseases all over the world. There are several treatment options for the management of these diseases. Some studies have reported that drugs used to manage diabetes and hypertension may have an impact on psychiatric disorders such as depression and dementia. In this article, we aimed to review the results of recent studies about the impact of anti-hypertensive and antidiabetic drugs on psychiatric disorders.